2017
DOI: 10.1016/j.redox.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Azidothymidine-triphosphate impairs mitochondrial dynamics by disrupting the quality control system

Abstract: Highly active anti-retrovirus therapy (HAART) has been used to block the progression and symptoms of human immunodeficiency virus infection. Although it decreases morbidity and mortality, clinical use of HAART has also been linked to various adverse effects such as severe cardiomyopathy resulting from compromised mitochondrial functioning. However, the mechanistic basis for these effects remains unclear. Here, we demonstrate that a key component of HAART, 3ꞌ-azido-3ꞌ-deoxythymidine (AZT), particularly, its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Thus, it is conceivable to expect that the potential cumulative side effects of NRTIs may lead to long-term tissue damage in the population aging with HIV/AIDS (13)(14)(15). In that regard, long-term therapy with zidovudine has been associated with a toxic mitochondrial myopathy (16) and myocyte mitochondrial dysfunction with increased ROS production, confirmed by both in vitro and in vivo studies (2,3,10,11,17,18).…”
mentioning
confidence: 90%
“…Thus, it is conceivable to expect that the potential cumulative side effects of NRTIs may lead to long-term tissue damage in the population aging with HIV/AIDS (13)(14)(15). In that regard, long-term therapy with zidovudine has been associated with a toxic mitochondrial myopathy (16) and myocyte mitochondrial dysfunction with increased ROS production, confirmed by both in vitro and in vivo studies (2,3,10,11,17,18).…”
mentioning
confidence: 90%
“…133 Moreover, anti-HIV therapies have also been shown to inhibit the mitochondrial fusion-fission cycle. 8 Local anesthetics have been suggested to interact with phospholipids on the mitochondrial membrane, which often result in increased membrane permeability, electron transport chain disruption, and calcium accumulation. 134 Growth factors and cytokine signaling Growth factors and cytokines are biologically active molecules that act directly on many cellular functions, such as adhesion, proliferation, and migration.…”
Section: Mitochondrial Toxicitymentioning
confidence: 99%
“…However, recent studies have shown that a considerable number of drugs in use can also disrupt cardiac function by impairing myocardial metabolism and cardiac structure. These include anticancer therapies associated with myocardial apoptosis, 5 neurodegenerative disease agents with severe risk of fibrotic valvular heart disease, 6 or anti-bacterial 7 and antiviral 8 treatments leading to mitochondrial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial fission is divided into the fission of membranes and outer membranes in mitochondria and is regulated by DRP1 ( 43 , 44 ). DRP1 is classified as a homologous protein of guanosine triphosphate (GTP) hydrolyzed enzyme (GTPase) power protein.…”
Section: The Physiological State Of Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%
“…Mitochondrial fusion is divided into outer membrane fusion and endometrial fusion. It is regulated by a variety of proteins, including mitofusin (MFN) in the outer membrane of mitochondria and optic atrophy protein 1 (OPA1) ( 44 , 45 , 49 , 51 , 56 61 ). Among them, mitofusin 1 (MFN1) and mitofusin 2 (MFN2) regulate mitochondrial outer membrane fusion.…”
Section: The Physiological State Of Mitochondrial Dynamics and Mitophagymentioning
confidence: 99%